Exploring the clinical efficacy and mechanism of high-position colon dialysis combined with Traditional Chinese Medicine retention enema in real-world patients with stage 3–5 chronic kidney disease (non-dialysis) based on the theory of the Gut–Kidney axis - Deng, Yanli; Zhang, Leixiao; Chen, Si; Xu, Dongxian; Wu, Wei; Shen, Tao; Liu, Zhen; Yang, Lin; Wen, Aiwei; Hou, Yuhao; Shao, Fanyun (Frontiers in Pharmacology, 2024)
Background: With societal and economic development, the annual incidence of chronic kidney disease (CKD) is increasing. Current treatments for CKD are limited, and once patients progress to the uraemic stage, it places a significant economic burden on families and society. Based on the "gutkidney axis" theory and real-world research, this study aims to evaluate the clinical efficacy, safety, and potential mechanism of high-position colon dialysis combined with traditional Chinese medicine (TCM) retention enema in treating stage 3-5 chronic kidney disease (non-dialysis). Additionally, it seeks to identify new therapeutic targets and approaches for CKD treatment. Methods: The TCM decoction was analyzed using Ultra-Performance Liquid Chromatography-Quadrupole-Orbitrap-High Resolution Mass Spectrometry (UPLC-Q-Orbitrap-HRMS). Participants meeting the inclusion criteria were divided into a control group (n=153) and a treatment group (n=159) based on their preferences and physicians' recommendations. Both groups adhered to a high-quality low-protein, low-salt, lowphosphorus, and low-fat diet supplemented with essential amino acids, and were monitored for blood pressure, blood glucose, and blood lipids. The treatment group received high-position colon dialysis combined with TCM retention enemas (administered at least 12 times every other day). Results:Thirteen compounds were identified from the herbs by UPLC-Q-Orbitrap-HRMS. The CKD3-5 treatment group exhibited improvements in blood biochemistry and other laboratory indices, with significant enhancements in renal function-related indices for CKD4 and CKD5 stages (P < 0.05).Following treatment, indoxyl sulfate (IS), endotoxin, and D-lactic acid levels decreased to a certain extent in both groups, with a statistically significant difference observed within the treatment group (P < 0.05). The treatment group displayed a significant reduction in aerobic bacterial colonies, an increase in anaerobic bacterial colonies, a decrease in Escherichia coli colonies, and an increase in Bifidobacterium and Lactobacillus colonies (P < 0.05). No significant changes in colony numbers were observed in the control group. Conclusion: High-position colon dialysis combined with TCM retention enema may serve as an adjuvant treatment for CKD4-5 (non-dialysis), and its mechanism may be related to the reduction of uraemic toxins, improvement of intestinal mucosal barrier function, and regulation of intestinal microecology.